The image enters the scene. Digital creations in the scenic field, urban space and natural space. (ASRI. Art and Society. Journal for Research in Arts and Digital Humanities, 2022)
Theater, dance, opera, circus, music, and visual arts are building new cartographies in the performing arts thanks to the insertion of ICTs in their immersive shows and generating new audiences. Our cities are filled with screens that mediate our perception. How are these new technological expressions intervening in the relationship with our environment? Light Festivals are becoming more common in our cities, as are immersive shows. This democratization of aesthetic enjoyment based on technological proposals is associated with the risk of confusing the artistic work with its staging, often spectacular and markedly virtuosic, making it necessary to critically reflect on this phenomenon. New technologies allow complex relationships to be established between the image, the scenic, natural or urban space. Visual experiences leave the screens of our personal devices and conquer new supports, formats, and creative proposals. Digital photography and video projections and interactive lighting effects offer us multiple possibilities for creation, interpretation, and innovation in the construction of experiential spaces. All these new artistic manifestations generate innovative and multidisciplinary research proposals. From a critical artistic point of view, this open call brings together those researchers who have dealt with the use of digital and analog images to create spaces or transform existing ones in search of new meanings in the field of image cultures.
Keywords: Theatre; videomapping; contemporary escenographies; audiovisual production; Arts and performaces